Preparation method and application of ceramic nanofiber membrane with catalytic ozonation function

By coating ceramic nanofibers on the ceramic membrane support and loading nanometal oxide catalysts, ceramic nanofiber membranes with high porosity and high specific surface area are prepared, which solves the problems of complex preparation processes of existing ceramic membranes and insufficient catalytic activity. , achieving efficient removal of emerging pollutants in the water.

CN119215689APending Publication Date: 2024-12-31TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411330476.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing ceramic membrane preparation process is complex, with low porosity and insufficient catalytic activity, making it difficult to effectively remove emerging pollutants in water.

Method used

A ceramic nanofiber is mixed with a dispersant and a film-forming agent to form a bilayer asymmetric structure. The supported catalyst is impregnated by the nanometal oxide precursor solution to prepare a ceramic nanofiber membrane with high porosity and high specific surface area.

Benefits of technology

The number of catalytically active sites and membrane strength are improved, the efficiency of removal of emerging pollutants in water bodies is significantly improved, the process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215689A_ABST
    Figure CN119215689A_ABST
Patent Text Reader

Abstract

A preparation method of a ceramic nanofiber membrane with a catalytic ozonation function comprises the following steps: S1, mixing ceramic nanofibers with a dispersing agent and a film-forming agent, coating a ceramic membrane support body with the mixture, and drying and sintering to form a ceramic nanofiber membrane with a double-layer asymmetric structure; s2, the ceramic nanofiber membrane with the efficient catalytic ozonation function is prepared through the processes of dipping, drying and firing the ceramic nanofiber membrane in a nano metal oxide precursor solution. The prepared ceramic nanofiber membrane with a double-layer asymmetric structure is taken as a basis, a nano metal oxide precursor solution is taken as a main raw material, and the ceramic nanofiber membrane with a catalytic ozonation function is prepared, so that the removal efficiency of pollutants, especially emerging pollutants such as sulfamethoxazole and tetracycline in a water body can be greatly improved; the problems that an existing catalytic ceramic membrane is low in catalytic efficiency, complex in preparation process, high in cost and the like are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment materials, and in particular to a preparation method and application of a ceramic nanofiber membrane with catalytic ozone oxidation function. Background Art

[0002] Ceramic membranes are widely used in the field of water treatment because of their excellent properties such as high temperature resistance, oxidation resistance, high mechanical strength, long service life and chemical corrosion resistance. At present, most commercial ceramic membranes adopt an asymmetric structure, consisting of a support, a transition layer and a separation layer, and the raw materials for preparing ceramic membranes are mostly granular inorganic materials. At the same time, in order to prevent the granular inorganic materials from leaking into the interior of the support, multiple dip coating or spraying processes (at least three layers) are adopted. Therefore, the preparation of existing ceramic membranes has the problems of complex preparation process and long cycle, and ceramic membranes are prone to dead-end holes, low porosity, low specific surface area and pure water flux.

[0003] The preparation of ceramic membranes with catalytic ozone oxidation function currently mainly adopts sol-gel method, dip coating process and blending method to coat nano metal oxides inside and on the surface of ceramic membranes. However, due to the agglomeration and particle size growth of nano metal oxides during high-temperature sintering, the specific surface area of ​​the ceramic membrane decreases, which leads to fewer active sites of the catalyst and reduced catalytic activity. Therefore, it is urgent to seek a preparation method for a ceramic membrane with catalytic ozone oxidation function that has high porosity, large specific surface area and pure water flux, high catalytic activity and is easy to industrialize.

[0004] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention

[0005] The main purpose of the present invention is to solve the problems existing in the above-mentioned background technology and to provide a preparation method and application of a ceramic nanofiber membrane with catalytic ozone oxidation function.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a ceramic nanofiber membrane having a catalytic ozone oxidation function comprises the following steps:

[0008] S1. The ceramic nanofibers are mixed with a dispersant and a film-forming agent, coated on a ceramic membrane support, and dried and sintered to form a double-layer asymmetric ceramic nanofiber membrane; preferably, the ceramic nanofibers are attapulgite nanofibers, inorganic ceramic nanofibers with a diameter of 20 to 50 nm;

[0009] S2. The ceramic nanofiber membrane is immersed in a nano-metal oxide precursor solution, dried and sintered at high temperature to load a nano-metal oxide catalyst on the ceramic nanofiber membrane, thereby obtaining a ceramic nanofiber membrane with high-efficiency catalytic ozone oxidation function.

[0010] The ceramic membrane support has an average pore size of 2-3 μm and a porosity of 30-40%, and is made of aluminum oxide, silicon oxide or zirconium oxide.

[0011] Step S1 specifically includes:

[0012] S11: adding a dispersant to deionized water to form a uniform mixed solution A;

[0013] S12: adding ceramic nanofibers to solution A, performing ultrasonic dispersion and magnetic stirring to form a uniformly mixed solution B;

[0014] S13: adding a film-forming agent to solution B to form a uniformly mixed and suspended stable coating slurry;

[0015] S14: The coating slurry is subjected to a degassing treatment; preferably, the degassing treatment is performed at a vacuum degree of -0.04 MPa for 10 minutes;

[0016] S15: coating on the surface of the ceramic membrane support to form a double-layer asymmetric structure; preferably, the coating time is 10 to 40 seconds;

[0017] S16: Drying and sintering to obtain the ceramic nanofiber membrane; preferably, after drying at 80°C for 12 hours, placing in a muffle furnace, sintering at 600°C, and keeping warm for 1 hour.

[0018] The dispersant is one or more of sodium pyrosulfate, sodium hexametaphosphate, polyvinyl pyrrolidone or polyethylene glycol, and the added amount thereof is 0.5-1.5wt.% of the mass of the ceramic fiber.

[0019] The film-forming agent is sodium carboxymethyl cellulose or high molecular weight polyethylene glycol, etc., and its addition amount is 0.05-0.2wt.% of the mass of the ceramic fiber.

[0020] The average pore size of the double-layer asymmetric ceramic nanofiber membrane is 20-35 nm, and the porosity is ≥50%.

[0021] Step S2 specifically includes:

[0022] S21: immersing the ceramic nanofiber membrane in a nano metal oxide precursor solution; preferably, immersing for 20 minutes, with a vacuum degree of -0.08 MPa;

[0023] S22: After impregnation, drain, dry, wash, and dry again; preferably, take out the saturated ceramic nanofiber membrane, drain the excess nano metal oxide precursor solution, put it into an oven at 90°C for 12 hours, take it out, wash it with ultrapure water until the eluted solution is neutral, and then put it into an oven at 100°C for 12 hours;

[0024] S23: sintering at high temperature to obtain a ceramic nanofiber membrane having a catalytic ozone oxidation function; preferably, the dried ceramic nanofiber membrane is sintered at 400-600° C. for 5 hours.

[0025] The nano metal oxide precursor solution is one or more of manganese nitrate, manganese chloride, cerium nitrate, copper nitrate, ferric chloride or titanium tetrachloride, and the concentration is 0.02-0.15 mol / L.

[0026] The size of the nano metal oxide catalyst is 3-5 nm.

[0027] A method for preparing a ceramic nanofiber membrane with catalytic ozone oxidation function is disclosed, and the ceramic nanofiber membrane prepared is used for catalytic ozone oxidation to remove pollutants.

[0028] The embodiments of the present invention have the following beneficial effects:

[0029] The present invention provides a method for preparing a ceramic nanofiber membrane with a catalytic ozone oxidation function, wherein the ceramic nanofiber is mixed with a dispersant and a film-forming agent, coated on a ceramic membrane support, dried and sintered to form a double-layer asymmetric ceramic nanofiber membrane, and based on the obtained double-layer asymmetric ceramic nanofiber membrane, a nano metal oxide precursor solution is used as the main raw material to prepare a ceramic nanofiber membrane with a catalytic ozone oxidation function, which can greatly improve the removal efficiency of pollutants in water (especially emerging pollutants such as sulfamethoxazole and tetracycline), and effectively solve the problems of low catalytic efficiency, complex process, and high cost in the preparation of existing catalytic ceramic membranes. Preferably, a high-performance ceramic nanofiber membrane is prepared with attapulgite nanofibers as the main raw material, and the pits with a size of about 4 nm on the surface of the attapulgite nanofibers are used to constrain the aggregation and particle size growth of nano metal oxides during the sintering process, thereby greatly improving the specific surface area and the number of catalytic active sites of the catalytic ceramic nanofiber membrane.

[0030] The catalytic functional ceramic nanofiber membrane prepared by the present invention has excellent properties such as simple process, low cost and high porosity, and has a positive role in promoting the industrial production and popularization and application of ceramic nanofiber membranes with catalytic ozone oxidation function.

[0031] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 SEM-EDS photos of the ceramic nanofiber membrane with catalytic ozone oxidation function prepared in Example 1. (a) Surface, (b) Surface-EDS, (c) Cross-section, (d) Cross-section-EDS. DETAILED DESCRIPTION

[0033] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.

[0034] The embodiment of the present invention provides a method for preparing a ceramic nanofiber membrane having a catalytic ozone oxidation function, comprising the following steps:

[0035] S1. The ceramic nanofibers are mixed with a dispersant and a film-forming agent, coated on a ceramic membrane support, and dried and sintered to form a double-layer asymmetric ceramic nanofiber membrane; preferably, the ceramic nanofibers are attapulgite nanofibers, inorganic ceramic nanofibers with a diameter of 20 to 50 nm;

[0036] S2. The ceramic nanofiber membrane is immersed in a nano-metal oxide precursor solution, dried and sintered at high temperature to load a nano-metal oxide catalyst on the ceramic nanofiber membrane, thereby obtaining a ceramic nanofiber membrane with high-efficiency catalytic ozone oxidation function.

[0037] The ceramic membrane support has an average pore size of 2-3 μm and a porosity of 30-40%, and is made of aluminum oxide, silicon oxide or zirconium oxide.

[0038] In some embodiments, step S1 specifically includes:

[0039] S11: adding a dispersant to deionized water to form a uniform mixed solution A; the dispersant is one or more of sodium pyrosulfate, sodium hexametaphosphate, polyvinyl pyrrolidone or polyethylene glycol, and the added amount is 0.5-1.5wt.% of the mass of the ceramic fiber.

[0040] S12: adding ceramic nanofibers to solution A, performing ultrasonic dispersion and magnetic stirring to form a uniformly mixed solution B.

[0041] S13: adding a film-forming agent to solution B to form a uniformly mixed and stably suspended coating slurry; the film-forming agent is sodium carboxymethyl cellulose or high molecular weight polyethylene glycol, etc., and its addition amount is 0.05-0.2wt.% of the mass of the ceramic fiber.

[0042] S14: The coating slurry is subjected to a degassing treatment; preferably, the degassing treatment is performed at a vacuum degree of -0.04 MPa for 10 minutes.

[0043] S15: coating on the surface of the ceramic membrane support to form a double-layer asymmetric structure; preferably, the coating time is 10 to 40 seconds.

[0044] S16: Drying and sintering to obtain the ceramic nanofiber membrane; preferably, after drying at 80°C for 12 hours, placing in a muffle furnace, sintering at 600°C, and keeping warm for 1 hour.

[0045] The average pore size of the double-layer asymmetric ceramic nanofiber membrane is 20-35 nm, and the porosity is ≥50%.

[0046] In some embodiments, step S2 specifically includes:

[0047] S21: Immersing the ceramic nanofiber membrane in a nano-metal oxide precursor solution; preferably, immersing for 20 minutes, with a vacuum degree of -0.08MPa; the nano-metal oxide precursor solution is one or more of manganese nitrate, manganese chloride, cerium nitrate, copper nitrate, ferric chloride or titanium tetrachloride, with a concentration of 0.02 to 0.15 mol / L.

[0048] S22: After impregnation, drain, dry, wash, and dry again; preferably, take out the saturated ceramic nanofiber membrane, drain the excess nano metal oxide precursor solution, put it into an oven at 90°C for 12 hours, take it out, wash it with ultrapure water until the eluted solution is neutral, and then put it into an oven at 100°C for 12 hours;

[0049] S23: sintering at high temperature to obtain a ceramic nanofiber membrane having a catalytic ozone oxidation function; preferably, the dried ceramic nanofiber membrane is sintered at 400-600° C. for 5 hours.

[0050] The size of the nano metal oxide catalyst is 3-5 nm.

[0051] The ceramic nanofiber membrane has high porosity and high specific surface area. At the same time, the ceramic nanofibers are interwoven to form a three-dimensional network structure, which further prevents the ceramic nanofibers from leaking into the pores of the support body and can effectively improve the strength of the membrane layer. As an inorganic fiber material, there are a large number of pits with a size of about 4nm on the surface of the attapulgite nanofiber. These pits can restrict the aggregation and growth of nano-metal oxides, forming metal oxide particles with a size of about 4nm, which can greatly increase the exposure of the active sites of the catalyst. At the same time, the attapulgite nanofibers are interwoven to form a ceramic nanofiber membrane with a three-dimensional network structure, which further strengthens the nano-confinement effect and improves the catalytic activity of the ceramic nanofiber membrane. Therefore, the catalytic ozone oxidation functional ceramic nanofiber membrane prepared based on attapulgite nanofibers has excellent properties such as high porosity, large specific surface area and high catalytic activity.

[0052] The embodiment of the present invention provides a preparation of a ceramic nanofiber membrane with a double-layer asymmetric structure and a preparation of a ceramic nanofiber membrane with a catalytic ozone oxidation function and its application in catalytic ozone oxidation to remove pollutants (especially emerging pollutants such as sulfamethoxazole and tetracycline). The ceramic nanofiber membrane is mainly composed of inorganic ceramic nanofibers with a diameter of 20 to 50 nm, and an appropriate amount of film-forming agent and dispersant are added. After uniform mixing, it is coated on the surface of a ceramic membrane support with an average pore size of 2 to 3 μm. After drying and sintering, a ceramic nanofiber membrane with a double-layer asymmetric structure is obtained. In addition, the present invention is based on the ceramic nanofiber membrane prepared above, with a nano-metal oxide precursor solution as the main raw material, and an immersion in-situ homogeneous precipitation method is used to prepare a ceramic nanofiber membrane with a catalytic ozone oxidation function, which greatly improves the removal efficiency of emerging pollutants in water. The present invention effectively solves the problems of low catalytic efficiency, complex process, and high cost in the preparation of existing catalytic ceramic membranes, and has a positive role in promoting the industrial production of ceramic nanofiber membranes with catalytic ozone oxidation functions and their promotion and application in the field of water treatment.

[0053] Example 1

[0054] The present invention provides a ceramic nanofiber membrane with catalytic ozone oxidation function, including the preparation of ceramic nanofiber membrane and the preparation of catalytic ceramic nanofiber membrane, wherein the support body used is prepared from alumina particles with an average pore size of 3 μm.

[0055] 1. The preparation of ceramic nanofiber membrane includes the following steps:

[0056] 60 mg of sodium hexametaphosphate was added to 100 mL of deionized water and magnetically stirred for 20 min (500 r / min) to obtain a uniformly mixed solution A;

[0057] 4 g of attapulgite was added to solution A, ultrasonically dispersed for 30 min, and then magnetically stirred for 60 min (500 r / min) to obtain a uniform mixed solution B;

[0058] 0.08 g of sodium carboxymethyl cellulose was added to solution B, and the mixture was stirred magnetically for 30 min (800 r / min) to form a stably suspended ceramic membrane slurry, and then degassed at a vacuum degree of -0.04 MPa for 10 min.

[0059] The stable coating slurry is coated on the surface of a ceramic membrane support with an average pore size of 3 μm, and the coating time is 15 s;

[0060] The wet ceramic nanofiber membrane was dried at 80℃ for 12h, fired at 600℃, kept for 1h, and cooled naturally. The obtained membrane surface was defect-free, with a porosity of 62%, a most probable pore size of 22nm, a membrane thickness of 10μm, and a pure water permeability of 118L / (m2·h·bar) double-layer asymmetric ceramic nanofiber membrane.

[0061] 2. The preparation of ceramic nanofiber membrane with catalytic ozone oxidation function includes the following steps:

[0062] 2.33 mL of manganese nitrate solution was added to 100 mL of deionized water, with a manganese nitrate concentration of 0.05 mol / L, and magnetic stirring was performed for 30 min (500 r / min) to obtain a uniformly mixed solution A;

[0063] The ceramic nanofiber membrane was immersed in solution A under a vacuum degree of -0.08 MPa for 20 min;

[0064] The saturated ceramic nanofiber membrane was taken out, the excess manganese nitrate solution was drained, and it was placed in a 90°C oven to dry for 12 h, then washed with ultrapure water until the eluted solution was neutral, and then placed in an oven to dry for 12 h at 100°C;

[0065] The dried ceramic nanofiber membrane was sintered at 500° C. for 5 h to obtain a ceramic nanofiber membrane (0.05Mn@CNM) with catalytic ozone oxidation function, and the size of nano manganese oxide particles was 3 to 5 nm.

[0066] Figure 1 SEM-EDS photos of the ceramic nanofiber membrane with catalytic ozone oxidation function prepared in Example 1. (a) Surface, (b) Surface-EDS, (c) Cross-section, (d) Cross-section-EDS.

[0067] Based on the above-prepared ceramic nanofiber membrane with catalytic ozone oxidation function, a continuous flow-dead end filtration device was used. Under the conditions of a reaction vessel volume of 160mm×45mm×260mm, a reaction solution of 1.2L, a flux of 35LMH, an ozone dosage of 10.5mg / L, and a sulfamethoxazole (SMX) concentration of 20mg / L, the catalytic degradation efficiency of the ceramic nanofiber membrane with catalytic ozone oxidation function on SMX reached more than 80%. Compared with the efficiency of ozone oxidation degradation of SMX alone under this condition, it was increased by about 50%. The prepared catalytic ceramic nanofiber membrane has excellent catalytic degradation performance for emerging pollutants in water bodies.

[0068] Example 2

[0069] The present invention provides a ceramic nanofiber membrane with catalytic ozone oxidation function, wherein the performance of the ceramic nanofiber membrane used is consistent with that in Example 1.

[0070] The preparation of the catalytic ozone oxidation functional ceramic nanofiber membrane includes the following steps:

[0071] Add 4.66 mL of manganese nitrate solution to 100 mL of deionized water, with a manganese nitrate concentration of 0.1 mol / L, and stir magnetically for 30 min (500 r / min) to obtain a uniformly mixed solution A;

[0072] The ceramic nanofiber membrane in Example 1 was immersed in solution A at a vacuum degree of -0.08 MPa for 20 min;

[0073] The saturated ceramic nanofiber membrane was taken out, the excess manganese nitrate solution was drained, and it was placed in a 90°C oven to dry for 12 h, then washed with ultrapure water until the eluted solution was neutral, and then placed in an oven to dry for 12 h at 100°C;

[0074] The dried ceramic nanofiber membrane was sintered at 500° C. for 5 h to obtain a ceramic nanofiber membrane (0.1Mn@CNM) with catalytic ozone oxidation function, and the size of nano manganese oxide particles was 3 to 5 nm.

[0075] Based on the ceramic nanofiber membrane with catalytic ozone oxidation function prepared above, a continuous flow-dead end filtration device was used. Under the conditions that the reaction container volume was 160mm×45mm×260mm, the reaction solution was maintained at 1.2L, the flux was 35LMH, the ozone dosage was 10.5mg / L, and the tetracycline (TC) concentration was 20mg / L, the catalytic degradation efficiency of TC by the ceramic nanofiber membrane with catalytic ozone oxidation function was 100%, indicating that the prepared catalytic functional ceramic nanofiber membrane has excellent catalytic degradation performance for emerging pollutants in water bodies.

[0076] Example 3

[0077] The present invention provides a ceramic nanofiber membrane with catalytic ozone oxidation function, wherein the performance of the ceramic nanofiber membrane used is consistent with that in Example 1.

[0078] The preparation of the catalytic ozone oxidation functional ceramic nanofiber membrane includes the following steps:

[0079] 2.33 mL of manganese nitrate solution was added to 100 mL of deionized water, with a manganese nitrate concentration of 0.05 mol / L, and magnetic stirring was performed for 30 min (500 r / min) to obtain a uniformly mixed solution A;

[0080] The ceramic nanofiber membrane in Example 1 was immersed in solution A at a vacuum degree of -0.08 MPa for 20 min;

[0081] The saturated ceramic nanofiber membrane was taken out, the excess manganese nitrate solution was drained, and it was placed in a 90°C oven to dry for 12 h, then washed with ultrapure water until the eluted solution was neutral, and then placed in an oven to dry for 12 h at 100°C;

[0082] The dried ceramic nanofiber membrane was sintered at 600° C. for 5 h to obtain a ceramic nanofiber membrane (0.05Mn@CNM) with catalytic ozone oxidation function, and the size of nano manganese oxide particles was 3 to 5 nm.

[0083] Based on the above-prepared ceramic nanofiber membrane with catalytic ozone oxidation function, a continuous flow-dead end filtration device was used. Under the conditions of a reaction vessel volume of 160mm×45mm×260mm, a reaction solution of 1.2L, a flux of 35LMH, an ozone dosage of 10.5mg / L, and a sulfamethoxazole (SMX) concentration of 20mg / L, the catalytic degradation efficiency of the ceramic nanofiber membrane with catalytic ozone oxidation function on SMX was about 60%. Compared with the efficiency of ozone oxidation degradation of SMX alone under this condition, it was increased by about 30%, indicating that the catalytic ceramic nanofiber membrane has excellent catalytic degradation performance on emerging pollutants in water bodies.

[0084] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, several equivalent substitutions or obvious variations can be made without departing from the concept of the present invention, and the performance or use is the same, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a ceramic nanofiber membrane having catalytic ozone oxidation function, characterized in that: The following steps are involved: S1. The ceramic nanofibers are mixed with a dispersant and a film-forming agent, coated on a ceramic membrane support, and dried and sintered to form a double-layer asymmetric ceramic nanofiber membrane; preferably, the ceramic nanofibers are attapulgite nanofibers, inorganic ceramic nanofibers with a diameter of 20 to 50 nm; S2. The ceramic nanofiber membrane is immersed in a nano-metal oxide precursor solution, dried and sintered at high temperature to load a nano-metal oxide catalyst on the ceramic nanofiber membrane, thereby obtaining a ceramic nanofiber membrane with high-efficiency catalytic ozone oxidation function.

2. The method for preparing a ceramic nanofiber membrane having a catalytic ozone oxidation function according to claim 1, characterized in that: The ceramic membrane support has an average pore size of 1 to 5 μm, preferably 2 to 3 μm, a porosity of 30 to 40%, and is made of aluminum oxide, silicon oxide or zirconium oxide.

3. The method for preparing a ceramic nanofiber membrane having catalytic ozone oxidation function according to claim 1 or 2, characterized in that: Step S1 specifically includes: S11: adding a dispersant to deionized water to form a uniform mixed solution A; S12: adding ceramic nanofibers to solution A, performing ultrasonic dispersion and magnetic stirring to form a uniformly mixed solution B; S13: adding a film-forming agent to solution B to form a uniformly mixed and suspended stable coating slurry; S14: The coating slurry is subjected to a degassing treatment; preferably, the degassing treatment is performed at a vacuum degree of -0.04 MPa for 10 minutes; S15: coating on the surface of the ceramic membrane support to form a double-layer asymmetric structure; preferably, the coating time is 10 to 40 seconds, more preferably 20 to 40 seconds; S16: Drying and sintering to obtain the ceramic nanofiber membrane; preferably, after drying at 80°C for 12 hours, placing in a muffle furnace, sintering at 500-700°C, more preferably at 600°C, and keeping warm for 1 hour.

4. The method for preparing a ceramic nanofiber membrane having a catalytic ozone oxidation function according to claim 3, characterized in that: The dispersant is one or more of sodium pyrosulfate, sodium hexametaphosphate, polyvinyl pyrrolidone or polyethylene glycol, and the added amount thereof is 0.5-1.5wt.% of the mass of the ceramic fiber.

5. The method for preparing a ceramic nanofiber membrane having a catalytic ozone oxidation function according to claim 3, characterized in that: The film-forming agent is sodium carboxymethyl cellulose or high molecular weight polyethylene glycol, etc., and its addition amount is 0.05-0.2wt.% of the mass of the ceramic fiber.

6. The method for preparing a ceramic nanofiber membrane having catalytic ozone oxidation function according to any one of claims 1 to 5, characterized in that: The average pore size of the double-layer asymmetric ceramic nanofiber membrane is 20-35 nm, and the porosity is ≥50%.

7. The method for preparing a ceramic nanofiber membrane having catalytic ozone oxidation function according to any one of claims 1 to 6, characterized in that: Step S2 specifically includes: S21: immersing the ceramic nanofiber membrane in a nano metal oxide precursor solution; preferably, immersing for 20 minutes, with a vacuum degree of -0.08 MPa; S22: After impregnation, drain, dry, wash, and dry again; preferably, take out the saturated ceramic nanofiber membrane, drain the excess nano metal oxide precursor solution, put it into an oven at 90°C for 12 hours, take it out, wash it with ultrapure water until the eluted solution is neutral, and then put it into an oven at 100°C for 12 hours; S23: sintering at high temperature to obtain a ceramic nanofiber membrane having a catalytic ozone oxidation function; preferably, the dried ceramic nanofiber membrane is sintered at 400-600° C. for 5 hours.

8. The method for preparing a ceramic nanofiber membrane having catalytic ozone oxidation function according to any one of claims 1 to 7, characterized in that: The nano metal oxide precursor solution is one or more of manganese nitrate, manganese chloride, cerium nitrate, copper nitrate, ferric chloride or titanium tetrachloride, and the concentration is 0.02-0.15 mol / L.

9. The method for preparing a ceramic nanofiber membrane having catalytic ozone oxidation function according to any one of claims 1 to 8, characterized in that: The size of the nano metal oxide catalyst is 3-5 nm.

10. Use of a ceramic nanofiber membrane prepared by the method for preparing a ceramic nanofiber membrane with catalytic ozone oxidation function as claimed in any one of claims 1 to 8 in removing pollutants by catalytic ozone oxidation.

Citation Information

Cited By

  • Multi-confinement catalytic ceramic nanofiber membrane as well as preparation method and application thereof

    CN119896977A

  • Multiple confined catalytic ceramic nanofiber membrane, preparation method and application thereof

    CN119896977B

  • High-efficiency ozone oxidation wastewater treatment method based on ceramic membrane

    CN121342200A